CXCR4 positive and angiogenic monocytes in myocardial infarction - Shantsila, Eduard; Tapp, Luke D.; Wrigley, Benjamin J.; Montoro-Garcia, Silvia; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2013)
Limited data are available on the role of monocytes in cardiac repair. In the present study, we evaluated the dynamic alterations of monocytes with reparative and angiogenic potential in patients with myocardial infarction(MI). Reparative CXCR4+ monocytes, and CD34+ and KDR+ monocytes with angiogenic potential derived from individual monocyte subsets were quantified by flow cytometry in patients with ST-elevation MI (n=50) and stable coronary artery disease (CAD, n=40). Parameters were measured on days 1, 3, 7 and 30 post MI. Monocyte subsets were defined as CD14++CD16–CCR2+ (‘classical’, Mon1), CD14++CD16+CCR2+ (‘intermediate’, Mon2), CD14+CD16++CCR2– (‘non-classical’, Mon3). Plasma levels of inflammatory cytokines, fibrinolytic factors and microparticles (MPs) were assessed on day 1. CXCR4+ and KDR+ monocytes were increased following MI, being more prominently associated with Mon2 (median[IQR] of CXCR4+ Mon2 60[25–126] per μl in STEMI vs. 27[21–41] per μl in stable CAD). The counts of CXCR4+ Mon2 in STEMI significantly reduced by day 30 of follow-up (27[18–47], p<0.001). Expression of the pro-reparative scavenger receptor CD163 on Mon3 was reduced in acute MI (p=0.008), and on other subsets later during the follow-up with lowest levels at day 3 post-MI (p<0.001 for Mon1, p=0.02 for Mon2). CD204 expression on Mon1 correlated with tissue type plasminogen activator levels (r=0.46, p=0.001). Interleukin(IL)6 levels correlated with counts of Mon2-derived CXCR4+ and KDR+ cells. Interleukin-1β correlated with KDR+ Mon2 counts. IL10 correlated with CXCR4+ Mon2 levels. Low count of CXCR4+ Mon2 and low CD163 expression by Mon2 were associated with higher ejection fraction six-weeks after MI. In conclusion, the Mon2 subset has the most prominent role in the observed changes in reparative monocytes in MI. The association of reparative monocytes with inflammatory/fibrinolytic markers indicates a complex interplay of these cells in the post-MI state.Note: The review process for this paper was fully handled by Prof. Christian Weber, Editor in Chief.
Keywords: Monocytes; myocardial infarction; CXCR4; endothelial progenitor cells